Relações entre confiança, valores organizacionais e engajamento no trabalho: um estudo com servidores públicos - Ribeiro, Laís Paranaiba Frattari (2017)
The literature suggests that employees are more likely to engage at work when they have high levels of trust and share organizational values. Thus, this study had as main objective to test the model in which engagement at the work is explained by the employee's trust in the organization and perception of organizational values in a sample of civil servants linked to the federal, state and municipal spheres. The sample consisted of 235 public servants from the three administrative spheres, with working and statutory working ties. After approval by the Ethics Committee, data were collected with reliable and valid instruments, which were analyzed through descriptive statistics and standard multiple regression, with engagement dimensions as criterion-variables. Among the results, there were levels of commitment and trust in moderate organizational ethics and competence. The most perceived values were compliance and prestige. The test of the model showed that confidence in the competence of the organization explained 25% of the variance of the force dimension, and trust in ethics and the value of well-being at work explained 18% of the absorptive dimension. The conclusions indicate that the proposed model was not confirmed, revealing that trust was a better predictor of engagement than organizational values. It is recommended that studies be carried out to verify how work engagement occurs in the administrative spheres, as well as the investigation of other explanatory variables about engagement at the work of public servants.